Barriers to an Information Effect on Diagnostic Disparities of Autism Spectrum Disorder in Young Children - David Schelly; Patricia Jiménez González; Pedro J. Solís (SAGE Publishing, 2019)
Objectives: Autism spectrum disorder (ASD) is underdiagnosed in children from minority and low socioeconomic status families, and reports indicate that parental "lack of awareness" of symptoms is a factor, which implicates the adoption of the category globally. However, parental knowledge of ASD has failed to explain emerging clusters of cases. The objective of the present research was to identify and describe barriers to an "information effect" in diagnosis. Methods: Interviews were conducted with the parents of 54 children with ASD in Costa Rica, many living within clusters that appeared after a genetic study conducted an information campaign for recruitment. The interviews explored factors influencing symptom recognition and help-seeking behaviors. Several barriers were identified that prevent information about ASD or exposure to diagnosed cases from influencing parents' help-seeking behaviors. Results: Early symptoms in most children gave parents no reason to suspect ASD. Later, parents' understanding of ASD depended on caricatures of the disorder. Parents often received unsolicited advice from strangers, although rarely from family, and it was always seen as critical of their parenting; furthermore, the advice was too late to influence the referral process, which was well underway by the time classical symptoms of ASD appeared, if they did at all. Postdiagnosis, the interviewees occasionally gave advice to other parents, mostly strangers, but none had apparently been diagnosed. Conclusions: The results implicate efforts to educate parents about symptoms of ASD, where a focus on generic developmental delays and neurodevelopmental disorders in general may be more effective than ASD-specific information.